Functional Studies of CCAAT/Enhancer Binding Protein Site Located Downstream of the Transcriptional Start Site - Yujie Liu; Michael R Nonnemacher; Aikaterini Alexaki; Vanessa Pirrone; Anupam Banerjee; Luna Li; Evelyn Kilareski; Brian Wigdahl (SAGE Publishing, 2017)
Previous studies have identified a CCAAT/enhancer binding protein (C/EBP) site located downstream of the transcriptional start site (DS3). The role of the DS3 element with respect to HIV-1 transactivation by Tat and viral replication has not been characterized. We have demonstrated that DS3 was a functional C/EBPβ binding site and mutation of this site to the C/EBP knockout DS3-9C variant showed lower HIV-1 long terminal repeat (LTR) transactivation by C/EBPβ. However, it was able to exhibit similar or even higher transcription levels by Tat compared to the parental LTR. C/EBPβ and Tat together further enhanced the transcription level of the parental LAI-LTR and DS3-9C LTR, with higher levels in the DS3-9C LTR. HIV molecular clone viruses carrying the DS3-9C variant LTR demonstrated a decreased replication capacity and delayed rate of replication. These results suggest that DS3 plays a role in virus transcriptional initiation and provides new insight into C/EBP regulation of HIV-1.